105. Hemodynamic (fNIRS), electrophysiological (EEG) and autonomic responses to affective pictures: A multi-method approach to the study of emotions. Issue 4 (April 2016) - Vanutelli, M.E.; Grippa, E.; Balconi, M.
Abstract : The activation of the prefrontal cortex during affective picture processing has been extensively studied in its temporal (by EEG), spatial (by neuroimaging studies), and peripheral (by autonomic system measures) features, even if little is known about the relation between neural measures, and between cortical and psychophysiological ones. Nonetheless, emotions and their multilevel processing need to be explored by means of a multi-method approach. The aim of the present study was to examine emotional processing in healthy adults, instructed to look at affective (positive and negative) IAPS pictures during simultaneous hemodynamic (near-infrared spectroscopy, fNIRS), EEG and autonomic activity recording. Twenty subjects participated in the experiment. Stimuli were presented for 6 s in a randomized order, with 12 s inter-stimulus interval. Our main results indicated a differential involvement of prefrontal areas (dorsolateral prefrontal cortex, DLPFC) according to the valence of the stimulus, and a relevant lateralization effect, with negative pictures inducing increased oxygenated hemoglobin (O2 Hb) and increased theta and delta activity (frequency band analysis) in the right hemisphere. Also, an increased systemic skin conductance response (SCR) emerged. Finally, an intrinsic relation was found and discussed between these three different levels.